2016
DOI: 10.1523/jneurosci.1628-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multisensory Integration Task Reveals Robust Deficits in Rodent Models of Schizophrenia: Converging Evidence for Remediation via Nicotinic Receptor Stimulation of Inhibitory Transmission in the Prefrontal Cortex

Abstract: Atypical multisensory integration is an understudied cognitive symptom in schizophrenia. Procedures to evaluate multisensory integration in rodent models are lacking. We developed a novel multisensory object oddity (MSO) task to assess multisensory integration in ketamine-treated rats, a well established model of schizophrenia. Ketamine-treated rats displayed a selective MSO task impairment with tactile-visual and olfactory-visual sensory combinations, whereas basic unisensory perception was unaffected. Orbito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 63 publications
2
32
1
Order By: Relevance
“…Similarly, acute MK-801-induced memory impairments in mice are improved by acute nicotine administration [189], while chronic nicotine reverses heightened impulsivity in a mouse chronic PCP model [190]. Finally, systemic and intra-orbitofrontal cortex administration of nicotine or the nAChR agonist ABT-418 dose-dependently ameliorates chronic ketamine-induced impairments in a multisensory integration task, and this effect is blocked by GABA-A receptor antagonism [191]. These effects appear dependent on parvalbumin interneurons in the orbitofrontal cortex, as silencing parvalbumin interneurons impairs multisensory integration task performance, and this is reversed by ABT-418 administration [191].…”
Section: Nicotinementioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, acute MK-801-induced memory impairments in mice are improved by acute nicotine administration [189], while chronic nicotine reverses heightened impulsivity in a mouse chronic PCP model [190]. Finally, systemic and intra-orbitofrontal cortex administration of nicotine or the nAChR agonist ABT-418 dose-dependently ameliorates chronic ketamine-induced impairments in a multisensory integration task, and this effect is blocked by GABA-A receptor antagonism [191]. These effects appear dependent on parvalbumin interneurons in the orbitofrontal cortex, as silencing parvalbumin interneurons impairs multisensory integration task performance, and this is reversed by ABT-418 administration [191].…”
Section: Nicotinementioning
confidence: 93%
“…Finally, systemic and intra-orbitofrontal cortex administration of nicotine or the nAChR agonist ABT-418 dose-dependently ameliorates chronic ketamine-induced impairments in a multisensory integration task, and this effect is blocked by GABA-A receptor antagonism [191]. These effects appear dependent on parvalbumin interneurons in the orbitofrontal cortex, as silencing parvalbumin interneurons impairs multisensory integration task performance, and this is reversed by ABT-418 administration [191]. Collectively, this suggests acute and chronic nicotine can improve cognitive impairment in an MK-801 schizophrenia rodent model, an effect which may depend on parvalbumin interneuron function in the PFC.…”
Section: Nicotinementioning
confidence: 97%
“…Processing sensory information into contextually rich representations of the environment is fundamental to cognition. The ability of the brain to generate a coherent representation of reality by consolidating simultaneously experienced stimuli from the same or different modalities is termed sensory integration (SI) or multisensory integration (MSI), respectively (Stein and Stanford 2008;Cloke et al 2016). Cognitive abnormalities are characteristic symptoms of brain disorders such as schizophrenia, autism, and epilepsy (Caplan et al 2008;Keefe and Harvey 2012;Leekam 2016).…”
mentioning
confidence: 99%
“…Indeed, MSI impairments are observed in neuropsychiatric populations (Oberman and Ramachandran 2008;Tseng et al 2015) and impaired SI of unimodal stimuli is also observed during some symptoms such as psychosis (Carter et al 2017). Despite the known deficits in MSI in human psychiatric populations, progress in this area has been hindered by a lack of valid behavioral assessments for animal models, particularly rodents (Cloke et al 2016). Considering the severity of cognitive symptoms in psychiatric illness correlate strongly with patient functional outcome (Tamminga et al 1998), the need for additional insight into the neural bases of MSI in both healthy and disease states is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation